Effect of Uniform Magnetic Field on Melting at Various Rayleigh Numbers - Dirbude, Sumer Bharat; Maurya, Vivek Kumar (Ital Publication, 2019)
Melting phenomena occurs in various industrial applications, such as metal castings of turbine blades, environmental engineering, PCM-based thermal storage devices, etc. During the design of these devices, they are designed for efficient heat transfer rate. To improve the heat transfer rate, understanding of the important flow processes during the melting (and solidification) is necessary. An objective of the present work is to study the effect of natural convection and magnetic field on interface morphology and thereby on melting rate. In this work, therefore, an effect of uniform transverse magnetic field on the melting inside a cavity, filled initially with solid gallium, at various Rayleigh numbers (Ra=3×105, 6×105, and 9×105) is presented. A 2D unsteady numerical simulation, with the enthalpy-porosity formulation, is performed using ANSYS-Fluent. The magnetic field is characterized by the Hartmann number (Ha) and the results are shown for the Ha = 0, 30 and 50. The horizontal walls of the cavity are considered insulated and vertical walls are respectively considered hot and cold. It is observed that the role of natural convection during the melting is significant on the temperature distribution and solid-liquid interface. The increased magnetic field (Ha = 30 and 50) found to have a suppressing effect on the dominance of natural convection at all Rayleigh numbers (Ra=3×105, 6×105, and 9×105).